1981
DOI: 10.1001/jama.1981.03320240031020
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Myocarditis Associated With Chlamydia trachomatis Infection

Abstract: Paired serum samples from six children with mild to fatal myocarditis have been studied in the microimmunofluorescence test for antibodies against Chlamydia trachomatis. Two patients with other known causes of myocarditis had no antibodies. The other four patients each had C trachomatis antibody. Two had high titer rises, and two with onset one to three months before the first serum sample was taken had level antibody titers. The study of serum from myocarditis patients was unplanned; they were part of a group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Besides the respiratory infection caused by this organism, interest has been focussed on a possible association with cardiac disease, including peri-, myo-and endocarditis [8][9][10]. Further research has suggested an association between C. Foundation) antigen were measured in a simplified microimmunofluorescence test as previously described [11].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the respiratory infection caused by this organism, interest has been focussed on a possible association with cardiac disease, including peri-, myo-and endocarditis [8][9][10]. Further research has suggested an association between C. Foundation) antigen were measured in a simplified microimmunofluorescence test as previously described [11].…”
Section: Introductionmentioning
confidence: 99%
“…Conjunctivitis, pneumonia, myocarditis, otitis media and other diseases may develop in neonates born to mothers infected with chlamydia [4,18]. The results of this study revealed that the prevalence of C. trachomatis is 11.3%.…”
Section: Discussionmentioning
confidence: 70%
“…A decision maker who considers pyloric stenosis to be more serious than its relative weight in our model, in general or in specific circumstances (for instance, a clinician or parent deciding about prophylaxis for an infant with higher-than-average anesthetic risk), would be less inclined to give erythromycin prophylaxis than the model suggests. On the other hand, if future studies confirm long-term consequences of neonatal chlamydia exposure, as have been suggested by studies [36][37][38] showing that infants with C trachomatis pneumonia may have long-term chronic pulmonary effects and by reports [39][40][41] of infants with neonatal chlamydia infection and myocarditis or sudden infant death syndrome, then the relative value of preventing C trachomatis infection would increase in comparison with avoiding pyloric stenosis.…”
Section: Commentmentioning
confidence: 80%